A single mutation in cyclodextrin glycosyltransferase from Paenibacillus barengoltzii changes cyclodextrin and maltooligosaccharides production. Issue 10 (23rd January 2019) - Castillo, JdlM; Caminata Landriel, S; Sánchez Costa, M; Taboga, O A; Berenguer, J; Hidalgo, A; Ferrarotti, S A; Costa, H
Abstract: Cyclodextrin glycosyltransferases (CGTases) are bacterial enzymes that catalyze starch conversion into cyclodextrins, which have several biotechnological applications including solubilization of hydrophobic compounds, masking of unpleasant odors and flavors in pharmaceutical preparations, and removal of cholesterol from food. Additionally, CGTases produce maltooligosaccharides, which are linear molecules with potential benefits for human health. Current research efforts are concentrated in the development of engineered enzymes with improved yield and/or particular product specificity. In this work, we analyzed the role of four residues of the CGTase from Paenibacillus barengoltzii as determinants of product specificity. Single mutations were introduced in the CGTase-encoding gene to obtain mutants A137V, A144V, L280A and M329I and the activity of recombinant proteins was evaluated. The residue at position 137 proved to be relevant for CGTase activity. Molecular dynamics studies demonstrated additionally that mutation A137V produces a perturbation in the catalytic site of the CGTase, which correlates with a 10-fold reduction in its catalytic efficiency. Moreover, this mutant showed increased production of maltooligosaccharides with a high degree of polymerization, mostly maltopentaose to maltoheptaose. Our results highlight the role of residue 137 as a determinant of product specificity in this CGTase and may be applied to the rational design of saccharide-producing enzymes.